The criminal perspective in the Constitution of 1824. Analysis of the actuality of its principles after 200 years of its promulgation - Valdés Rivera, José Luis (Revista Internacional & Comparada de Derechos Humanos, 2024)
This paper aims to analyze the criminal and criminal procedural guarantees of the Constitution of 1824, its contents’ validity, and to compare it with the current legislation. This analysis is because, in recent months, several constitutional reforms have been discussed, and even the Constitution of 1824 has been pointed out as a model to follow to adapt the current Constitution to the contents of that one. Therefore, it is pertinent to conduct an analysis from a criminal perspective in this case to understand the scope of that two-century-old legislation regarding human rights protection.
Keywords: Constitution; crimes; guarantees; laws; prison sentence